Improvement of the environmental protection in the mine area by the monitoring automatization of the flowing water quality - Brčić Krsta (Bakar, 2023)
The environmental protection and renewable energy sources are the priority of all investments around the world. The environmental monitoring systems are equipped with various sensors, devices, networks and software to collect, process, monitor and display data on the environmental parameters. In that sense, this paper discusses the automation of river water quality monitoring in the area of the "Čukaru Peki" copper mine in Serbia. Until now, the water quality in the area is being monitored by taking and analyzing the water samples in the competent laboratory. The automation would improve the quality of monitoring multiple times. At the same time, the significantly cheaper ("low cost") devices can be used. These devices are cheaper and their quality is for a specific application completely at the level of those offered on the market as commercial pnes. The problem is briefly considered in terms of costs and benefits.